Herbal versus synthetic drugs; beliefs and facts - Karimi Ali; Majlesi Maedeh; Rafieian-Kopaei Mahmoud (Society of Diabetic Nephropathy Prevention, 2015)
Herbal therapy is a holistic therapy, integrating emotional, mental and spiritual levels. Life style, emotional, mental and spiritual considerations are part of any naturopathic approach. The use of herbs does not generally involve "drug" actions or adverse effects. Although medicinal plants are widely used and assumed to be safe, however, they can potentially be toxic. Where poisoning from medicinal plants has been reported, it usually has been due to misidentification of the plants in the form, in which they are sold, or incorrectly preparation and administration by inadequately trained personnel. There are some "drug like" plants remedies that their actions approach that of pharmaceuticals. Herbalists use these plants in treatment strategies and in countries such as Britain their vast availability is restricted by law. Digitalis is one of these examples and the number of these plants is not a lot. The mechanisms by which the herbs generally act are not established, however, most of medicinal plants possess antioxidant activities. The plants have been shown to effective by this property is various conditions including cancer, memory deficit and Alzheimer, atherosclerosis, diabetes and other cardiovascular diseases. Antioxidant activities of herbal medicines are also effective in reducing the toxicities of toxic agents or other drugs.